Magnetorheological elastomers berbasis lateks cair sebagai matriks utama - Virel Wibawa; U Ubaidillah (Badan Kerja Sama Teknik Mesin Indonesia, 2019)
This study tells about isotropic MRE with latex as the matrix, variation on the mass fraction of CI particle (wt%) and evaluate the following characteristics, such as density, hardness, break stress, elongation and swelling of the variation ratio mixture of MRE with the latex matrix. In this study use 0, 30, 40, 50, 60 and 70 wt% as the MRE composition, held in Laboratorium Pusat Penelitian Karet Indonesia which has the standardized rubber testing in yield strength, hardness and swelling in Indonesia. Pure latex with 0,94 gr/cm3 in density, improvement above 100% happens when CI particle added as much as 40%. The amount of CI particle made the rising of hardness point as much as 15 point from 35 when CI particle added as much as 70%. The add of CI particle cause a decresing of tensile stress, it’s seen when pure latex has 14,5 MPa in tensile testing and breakdown until 760%. When CI particle added as much as 70%, the break stress decrease until 2 MPa and the breakdown in 610%. Volume changes when the pure latex sink in the ASTM OIL 3 liquid, the volume increase as much as 167,94% and still increase almost 100% in 305,97% when CI particle 70% added.